The role of eddies in the Southern Ocean temperature response to the southern annular mode - Screen, James A.; Gillett, Nathan P.; Stevens, David P.; Marshall, Gareth J.; Roscoe, Howard K. (Journal of Climate, 2009)
© Copyright 2009 American Meteorological Society (AMS). Permission to use figures, tables, and brief excerpts from this work in scientific and educational works is hereby granted provided that the source is acknowledged. Any use of material in this work that is determined to be “fair use” under Section 107 of the U.S. Copyright Act September 2010 Page 2 or that satisfies the conditions specified in Section 108 of the U.S. Copyright Act (17 USC §108, as revised by P.L. 94-553) does not require the AMS’s permission. Republication, systematic reproduction, posting in electronic form, such as on a web site or in a searchable database, or other uses of this material, except as exempted by the above statement, requires written permission or a license from the AMS. Additional details are provided in the AMS Copyright Policy, available on the AMS Web site located at (http://www.ametsoc.org/) or from the AMS at 617-227-2425 or copyrights@ametsoc.org. The role of eddies in modulating the Southern Ocean response to the southern annular mode (SAM) is examined, using an ocean model run at multiple resolutions from coarse to eddy resolving. The high-resolution versions of the model show an increase in eddy kinetic energy that peaks 2–3 yr after a positive anomaly in the SAM index. Previous work has shown that the instantaneous temperature response to the SAM is characterized by predominant cooling south of 45°S and warming to the north. At all resolutions the model captures this temperature response. This response is also evident in the coarse-resolution implementation of the model with no eddy mixing parameterization, showing that eddies do not play an important role in the instantaneous response. On the longer time scales, an intensification of the mesoscale eddy field occurs, which causes enhanced poleward heat flux and drives warming south of the oceanic Polar Front. This warming is of greater magnitude and occurs for a longer period than the initial cooling response. The results demonstrate that this warming is surface ...